1992
DOI: 10.1002/chir.530040606
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical studies of chiral h‐1 antagonists of histamine: The resolution, chiral analysis, and biological evaluation of four antipodal pairs

Abstract: The resolution of the H-1 antihistamines chloropheniramine, dimethindene, carbinoxamine, and mebrophenhydramine is described. The optical purity of antipodal products is investigated by chiral HPLC (use of alpha 1-acid glycoprotein and beta-cyclodextrin columns) and NMR (spectra of beta-cyclodextrin inclusion complexes). Configurational relationships among the group are reviewed and assignments are confirmed and extended by circular dichroism evidence. Affinity constants of antipodal pairs for guinea pig ileum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(28 citation statements)
references
References 20 publications
(5 reference statements)
0
26
0
2
Order By: Relevance
“…Chiral diarylmethanols are constituents of biologically active compounds such as clemastine, [26] neobenodine, [27] and chloropheniramine. [28Ϫ30] Enantioselective syntheses of diarylmethanols use either asymmetric catalytic hydrogenation of diarylketones [31,32] or enantioselective addition of arylzinc reagents to benzaldehydes in the presence of chiral catalysts.…”
Section: Asymmetric Synthesis Of (S)-neobenodinementioning
confidence: 99%
“…Chiral diarylmethanols are constituents of biologically active compounds such as clemastine, [26] neobenodine, [27] and chloropheniramine. [28Ϫ30] Enantioselective syntheses of diarylmethanols use either asymmetric catalytic hydrogenation of diarylketones [31,32] or enantioselective addition of arylzinc reagents to benzaldehydes in the presence of chiral catalysts.…”
Section: Asymmetric Synthesis Of (S)-neobenodinementioning
confidence: 99%
“…Ethanolamine class of H 1 antihistamines were proven to show stereoselectivity in binding to the receptors (Casy et al 1992). Doxylamine which is a similar kind of molecule to that of carbinoxamine showed that its (d) or (+) form has more binding affinity compared to its antipode (Tadiboyina et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Due to the advantages of organoboron reagents such as low toxicity, superior stability, and widespread availability, [16][17][18] and the significance of adducts as intermediates for the synthesis of biologically active compounds, [19][20][21] several types of active catalysts have been developed for this kind of reaction, such as palladium, 22) nickel, 23) and copper 24) complexes in addition to recently found effective metal species following our report. [25][26][27][28] However, they did not achieve adequate level performance and high catalyst loading was usually required to obtain sufficient results.…”
Section: Reviewmentioning
confidence: 90%